Post-Marketing Quality Control of Different Brands of Paracetamol and Paracetamol Plus Caffeine Tablets Available in Libyan Markets - Zaema Elbaroudi,; Omar Rbeida,; Ruwida Kamour,; Rashad Ghrew,; Nada Al-Dali,; Raniem Gammo, (AlQalam Journal of Medical and Applied Sciences, 2024)
Paracetamol (PA) is a widely used non-prescription analgesic and antipyretic medicine. This active pharmaceutical ingredient (API) available alone or in a combination formula as with caffeine (CA). Hence, it is essential to evaluate and compare the quality control parameters for different brands of paracetamol and paracetamol+caffeine tablets in order to assess their effectiveness. This study tested six tablets’ brands have both formulations, which are popular brands available in Tripoli retail pharmacies. Physical and chemical parameters were examined as a post marketing evaluation. The chemical tests included identification by Fourier-transform infrared (FTIR) spectroscopy and assay of drug content using UV-Vis spectroscopy for tablets of paracetamol labeled with A1, B1 and C1. However, physical analysis done for both brands, that containing paracetamol only (A1, B, and C1) and tablets of paracetamol plus caffeine (A2, B2 and C2), which included evaluation of appearance, weight variation, hardness, disintegration time and dissolution test. The results obtained showed that all the brands showed acceptable parameters according to Pharmacopeial specifications, and showed diverse physical properties. All brands demonstrated sufficient mechanical strength to resist fracture and crumbling. Additionally, samples were in compliance with the specifications of disintegration time and weight variation test. However, the chemical testing for the percent content according to BP2008 showed that product B1 was not comply with pharmacopoeia specifications with lowest API content of 91.2%. On the other hand, dissolution test revealed that the sample A2 (99%), C2(100%) paracetamol/caffeine had better release at 40 mints than brand A1(90%), C1(96%) tablets containing paracetamol only. Whereas, brands B2 (92.2%) paracetamol/caffeine tablets dissolved in slower rate compared with brand B1(92.76%) containing paracetamol alone. The results of this study indicated that the brands of Paracetamol and paracetamol combined with caffeine tablets available in the Tripoli drug market cannot be used interchangeably. الباراسيتامول هو دواء مسكن وخافض للحرارة يُستخدم على نطاق واسع ويمكن صرفه بدون بوصفة طبية. هذه المادة الفعالة متوفرة إما بمفردها أو في تركيبة مع مادة الكافيين. لذلك، من الضروري تقييم ومقارنة معايير الجودة للعلامات التجارية المختلفة لأقراص الباراسيتامول والباراسيتامول مع الكافيين لتقييم فعاليتها. في هذه الدراسة، تم اختبار ستة شركات تجارية للأقراص التي تحتوي على التركيبتين، والتي تُعد من العلامات التجارية الشهيرة المتوفرة في صيدليات طرابلس- ليبيا. تم فحص المعايير الفيزيائية والكيميائية كجزء من تقييم ما بعد التسويق. شملت الاختبارات الكيميائية التحقق من وجود المادة الفعالة باستخدام التحليل الطيفي بالأشعة تحت الحمراء باستخدام وتحديد نسبة تواجد المادة الفعالة باستخدام التحليل الطيفي للأشعة فوق البنفسجية لأقراص الباراسيتامول المسجلة باسم A1 وB1 وC1. أما التحليل الفيزيائي فقد تم إجراؤه على العلامات التجارية التي تحتوي فقط على الباراسيتامول A1 وB وC1 والتي تحتوي علي الباراسيتامول مع الكافيين (A2 وB2 وC2)، وشمل تقييم المظهر، التفاوت في الوزن، الصلابة، وقت التفكك، واختبار الذوبان. أظهرت النتائج التي تم الحصول عليها أن جميع العلامات التجارية أظهرت معايير مقبولة وفقًا لمواصفات الصيدلة، وأظهرت خصائص فيزيائية متنوعة. أظهرت جميع العلامات التجارية قوة ميكانيكية كافية لتحمل الكسور والتفتت. بالإضافة إلى ذلك، كانت العينات متوافقة مع مواصفات اختبار وقت التفكك واختبار التفاوت في الوزن. ومع ذلك، أظهر الاختبار الكيميائي لمحتوى المادة الفعالة وفقًا للـ BP2008 أن المنتج B1 لم يتوافق مع مواصفات الصيدلة بمحتوى أقل للمادة الفعالة بنسبة 91.2%. من ناحية أخرى، أظهر اختبار الذوبان أن العينة A2 (99%) وC2 (100%) من الباراسيتامول/الكافيين كانت تُطلق المادة بشكل أفضل بعد 40 دقيقة مقارنة بالعلامات التجارية A1 (90%) وC1 (96%) التي تحتوي على الباراسيتامول فقط. بينما ذابت أقراص العلامة التجارية B2 (92.2%) من الباراسيتامول/الكافيين بمعدل أبطأ مقارنة بالعلامة التجارية B1 (92.76%) التي تحتوي على الباراسيتامول فقط. أظهرت نتائج هذه الدراسة أن العلامات التجارية لأقراص الباراسيتامول وأقراص الباراسيتامول المدموجة مع الكافيين المتوفرة في سوق الأدوية في طرابلس لا يمكن استخدامها بالتبادل